Elevated stress hyperglycemia ratio associated with higher hospital mortality in patients with respiratory failure - Huihui Bai; Dan Niu; Boling Li; Yuan Zong; Yan Wang (Scientific Reports)
Abstract The stress hyperglycemia ratio (SHR) represents an emerging biomarker linked to poor clinical outcomes. However, its association with fatal outcomes in patients experiencing respiratory failure (RF) remains poorly understood. This research was designed to evaluate the utility of SHR in predicting both in-hospital mortality and intensive care unit (ICU) mortality among RF patients. This retrospective cohort analysis utilized data from the MIMIC-IV version 3.0 database. Patients diagnosed with RF in the ICU were divided into four groups according to the SHR index quartiles (group1, group2, group3, and group4), and the outcomes were in-hospital and ICU mortality. Survival outcomes among different groups were analyzed through Kaplan-Meier curves. Based on the results of the schoenfeld residual test, choose the Cox model or the model with the time interaction term to report the association between SHR and the outcome. Furthermore, restricted cubic splines analyses were conducted to explore potential non-linear relationships of SHR with both in-hospital and ICU mortality. This study enrolled 2,250 participants, demonstrating in-hospital mortality and ICU mortality rates of 23.91% and 14.31%, respectively. Kaplan-Meier analysis revealed that the group4 exhibited the lowest survival rates (P < 0.001). Through multivariate Cox regression, when comparing the group1 to the group4, three analytical models consistently showed increased in-hospital and ICU mortality in group4. The time interaction model revealed significant increases in hospital mortality risk across SHR quartiles compared to group1. Specifically, in model1, group2 showed a 62%-69% higher risk (HR = 1.69, 95% CI: 1.17–2.44), group3 exhibited a 358%-370% higher risk (HR = 4.58, 95% CI: 1.83–11.5) ,while group4 demonstrated exponential risk escalation. All quartile groups exhibited a daily risk attenuation of approximately 57% (time interaction term HR = 0.43, all p < 0.001). The associations remained consistent after adjusting the variables in models 2 and 3. In contrast, no significant risk association was observed between SHR and ICU mortality in the time interaction model. Besides, a U-shaped relationship was observed between SHR and both in-hospital mortality and ICU mortality. The study revealed that elevated SHR levels in ICU-admitted RF patients were significantly associated with increased risks of in-hospital mortality. Clinicians should closely monitor patients with high admission SHR values, especially patients in the highest SHR quantile (Q4 group) during the early admission period, underscoring the need for prioritized clinical intervention in this high-risk population.